Lower Limb Power, Strength, and BMI for Student Athletes' Physical Development - Agil Kusuma Wardhana; Fajar Awang Irawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aimed to analyze the profile of lower limb explosive power, lower limb muscle strength, and body mass index (BMI) of Sports Science student athletes. The study employed a quantitative method with a descriptive approach. The re-search sample consisted of 48 male student athletes selected using purposive sampling techniques. Data collection was conducted through direct testing and measurements, including the Jump DF test to measure lower limb explosive pow-er, a leg dynamometer to assess lower limb muscle strength, and body height and weight measurements to calculate body mass index. The data were analyzed using descriptive statistics, including mean, standard deviation, minimum value, maximum value, frequency, and percentage. The results showed that the average Jump DF score was 56.7 cm, with the majority of students categorized as Good (54.17%) and Excellent (20.83%). The average leg dynamometer result was 155.5 kg, with most students categorized as Excellent (75.00%) and Good (25.00%). The average BMI was 22.3 kg/m², with the majority of students classified as Normal (56.25%). The findings of this study indicate that male student athletes possess good lower limb explosive power, very good lower limb muscle strength, and predominantly normal BMI values. The results also revealed that lower limb mus-cle strength tended to be more dominant than lower limb explosive power. Therefore, physical development programs should focus on converting strength into explosive ability through power and plyometric training. These findings may serve as a basis for designing physical development programs for student ath-letes.